(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
The effect of paroxetine on the day-night variations in the synthesis of 5-hydroxytryptamine was determined in the rat brain in an effort to gain an insight into the mechanism of action of this drug. This was done by determining its effect on the activity of tryptophan hydroxylase, the rate-limiting enzyme in the biosynthesis of 5-hydroxytryptamine in serotonergic neurons. The enzyme activity was determined in two brain regions, cortex and the brainstem, at two time points of 12 h light/12 h dark cycle, namely, mid-light and middark. The results obtained showed that the activity of tryptophan hydroxylase was significantly greater in control animals during the dark than light phase both in the cortex and brainstem. They also demonstrate that the rate of synthesis of 5-hydroxytryptamine was affected by paroxetine in a time-dependent manner. It was therefore concluded that these time-dependent changes observed in paroxetine effect may influence the activity of serotonergic input into the suprachiasmatic nucleus and hence the regulation or expression of certain circadian rhythms. This action may help correct or compensate for abnormalities present in depressive illness.